The analysis of the power loss in a zero-voltage switching two-inductor boost cell operating under different circuit parameters - Li, Q.; Wolfs, Peter (IEEE, 2005)
This paper studies a comprehensive set of power loss components in a current fed zero-voltage switching (ZVS) two-inductor boost cell and presents a power loss optimisation method. The ZVS two-inductor boost cell is fed from a sinusoidally modulated two-phase synchronous buck converter with an interphase transformer (IPT). The ZVS boost cell produces a rectified sinusoidal voltage, which can be applied to an unfolding stage to generate grid compatible voltage as part of a module integrated photovoltaic inverter. This paper conducts the numerical analysis of the average power loss and establishes a set of circuit parameters for an optimized operating point, which results in the minimal power loss in the ZVS boost cell. The experimental results for a 1 MHz 100 W ZVS two-inductor boost converter is presented